Comic license in contemporary African American visual art. Issue 2 (2nd July 2020) - Sullivan, Emma
Abstract: Given a dominant visual discourse predicated upon stereotypes concerning menace, sexualisation, and abjection, African American visual production is often obligated to effect a correction by producing responsible, even didactic art. While this imperative remains a potent force, in this paper I focus upon work that is determinedly irreverent, even comic in its forthright address of race. My case studies are three African American artists: William Pope.L, a performance artist self-styled as the "Friendliest Black Artist in America"; a visual artist, Sanford Biggers, and a conceptual artist, Dave McKenzie. I suggest that all three create work that, in favouring the comic rather than the tragic modality, extends the affective possibilities for black expression. The comedy is not necessarily about generating laughter, rather, as a form of what Lauren Berlant calls 'deadpan aesthetic, ' its ambivalence engenders a deliberate and productive uncertainty.